Determining Criteria for Supplier Selection in the Indonesian Oil and Gas Industry - Habibah, Nur; Kusumastuti, Ratih Dyah (UI Scholars Hub, 2020)
Research Aims - This research aims to identify the main criteria of supplier selection in the oil and gas industry in Indonesia and their causal relationships by using the DEMATEL method. Methodology - Based on the literature review and discussions with experts, ten supplier selection criteria were identified and used as the basis of questionnaire development. The questionnaire was distributed to 57 respondents representing supply chain management and other divisions in eight oil and gas companies in Indonesia, with 51 valid responses. The data was analyzed using the DEMATEL method. Research Findings - The results show that product price is the most important criterion, while technical ability was the least important criterion. Moreover, six criteria (product quality, product price, technical ability, service, production capability, and financial situation) were identified as the cause criteria and require more attention compared to the other four effect criteria (delivery performance, stable delivery of goods, lead time, and reaction to demand change in time). Theoretical Contribution/Originality - The research provides insights on the important criteria of supplier selection in oil and gas companies in Indonesia and their causal relationships. Managerial Implications in the Southeast Asian Context - The results can be used by oil and gas companies to better select their suppliers. Research Limitations and Implications - This study uses a non-stratified sample from eight oil and gas companies in Indonesia, which may not accurately represent the Indonesian oil and gas industry.